Properties of Lightweight Matrix Using Industrial by-Products according to Mixing Ratio of NaOH and KOH - Hyun Shin, Jin; Gyu, Won; Soo Lee, Sang (International Journal of Engineering and Technology, 2018)
Background/Objectives:When producing 1 ton of cement, it produces 0.9 tons of carbon dioxide, so it is very important to reduce the use of cement or to find an alternative material.Methods/Statistical analysis: In order to replace cement which is frequently used to make lightweight cured products, blends of blast furnace slag, polysilicon and paper ash were used as binders. In order to stimulate the hardening of blast furnace slag, comparative analysis of characteristics of alkali stimulants was carried out by using KOH and NaOH as alkali stimulants.Findings: In order to improve the foaming performance for the production of lightweight Matrix, we used polysilicon and paper ash as well as blast furnace slag as one of industrial by - product a binder. KOH and NaOH were used as alkali stimulants. The experimental results are as follows.When alkali stimulants are used, the density decreases and the absorption rate increases. It is considered that the use of an alkali stimulant causes air bubbles to occur, resulting in a lower density and an increased absorption rate. The use of NaOH rather than KOH seems to result in better bubble generation. Strength was significantly decreased when alkali stimulants were used, but it was confirmed that the strength of NaOH was increased than that of KOH.Improvements/Applications: As a result of this study, we will fabricate a lightweight matrix that can be used as a prototype by using NaOH according to KS F 2701 standards.Â